Clinical anatomy of the shoulder after treatment for breast cancer. Issue 3 (8th July 2013) - Shamley, Delva; Lascurain‐Aguirrebeña, Ion; Oskrochi, Reza
<x xml:space="preserve">Abstract</x> Normal painfree movement of the upper limb requires movement at the glenohumeral joint and movement of the scapula on the thorax. Co‐ordinated movement of these joints is known as the scapulohumeral rhythm and is required during elevation of the arm. Coordinated movement is further achieved by timing of the many muscles acting across the joints. A pilot study from our laboratory has shown significant alterations to this scapulohumeral rhythm and its muscle control following treatment for breast cancer. The aims of this study were to: (1) correlate altered muscle activity from a larger sample with observed movement deviations; (2) compare movement and muscle deviations in survivors with a healthy population and (3) explore the impact of a mastectomy versus a wide local excision (WLE) on the observed deviations. Cross‐sectional study. 155 women treated for unilateral carcinoma of the breast and 21 age‐matched healthy women were included in the study. All patients filled out the Shoulder Pain and Disability Index (SPADI). Three‐dimensional kinematic data and EMG muscle activity were recorded during scaption on the affected and unaffected side. Patients demonstrated a different movement dysfunction depending on whether the left or the right shoulder was affected. Left affected shoulders demonstrated the greatest degree of internal rotation of all shoulders studied. Compared to healthy shoulders patients following a mastectomy demonstrated increased activity in both the left and right affected shoulders in all the measured muscles. In patients having a WLE, such increases were not observed in serratus anterior and pectoralis major activity on the right affected shoulder, where a decrease was noted. Muscle dysfunction was also observed in the unaffected side of patients. Having received chemotherapy contributed significantly to the difference seen between the affected and unaffected shoulders in patients. Differences in scapular tilt between affected and unaffected shoulders in patients were significantly associated with pain and disability, and changes in serratus anterior activity. Patterns of movement deviation resemble those seen in known shoulder conditions. Anatomical and biomechanical evidence supports the need for integrated rehabilitation and surveillance systems for the shoulder in oncology units. Clin. Anat. 27:467–477, 2014. © 2013 Wiley Periodicals, Inc.